Gestión del conocimiento y Universidad como institución generadora de conocimiento - Amaya Ocampo, Waldimar Alexander; Pérez Castillo, José Nelson (Ingeniería, 2008)
The knowledge managment is at the present time a topic of great relevance, with applicability in different areas, in those where the primordial objective is the intellectual growth and in which the objective is the lucre that one can obtain and that thanks to the Technologies of the Information and the Communication (TICs) they have become a viable reality. It is a tool that the productivity increases by means of specific clear and political positions that take to a maximum use of the resources. The knowledge managment refers, especially, to the use of an intangible capital before wasted or underemployed as era the knowledge in its different expressions. Inside this articulate it is considered the evolution that has had the concept of knowledge through the history, then it will be described the pattern of the cycle of life of the knowledge like fundamental factor to understand the because of the knowledge Management and finally it will be carried out an analysis of their applicability in the environment of the University.